INTEGRATING AUTHENTIC MATERIALS TO ENHANCE LISTENING COMPREHENSION: EVIDENCE FROM SECONDARY EFL CLASSROOMS IN INDONESIA - Wulandari, Indah; Safitri, Loli; Syafitri, Widya; Syahrul (ELP (Journal of English Language Pedagogy), 2025)
This study aims to examine the effect of using authentic materials on the listening skills of tenth-grade students at SMAN 1 Kamang Magek. The research was motivated by students’ difficulty in understanding spoken English due to limited exposure to the language used in real-life contexts. A quasi-experimental design was employed, involving two groups: an experimental class taught using authentic materials and a control class taught using conventional methods. Each group consisted of 27 students and underwent four instructional meetings. Data were collected through pre-tests and post-tests, then analyzed using SPSS with the Wilcoxon and Mann-Whitney tests. The results revealed that the use of authentic materials significantly improved students' listening skills. This was evident from the higher post-test scores of the experimental group compared to the control group. The findings suggest that authentic materials not only enhance listening comprehension but also expose learners to real-life English usage, including accent, intonation, and contextual meaning. It is therefore recommended that teachers incorporate authentic materials into their teaching to better prepare students for real-world communication.